Analisis Keputusan Pembelian terhadap Lemang Batok Berdasarkan Kemasan, Cita Rasa, dan Harga - Lilinesia Lilinesia (Mahesa Research Center, 2021)
This research was conducted with the aim of knowing whether the packaging affects the decision to purchase lemang batok in Tebing Tinggi City. And to find out whether the taste simultaneously influences the decision to buy lemang batoks in Tebing Tinggi Municipality. This is to determine whether the price has a partial effect on the decision to purchase lemang shells in Tebing Tinggi City. To find out whether, taste, and price affect the decision to buy lemang batok in Tebing Tinggi City. The research method uses a quantitative approach. This study uses multiple linear regression analysis techniques. Data sources are divided into two, namely primary and secondary. The results obtained (1) packaging has a significant effect, with the results of t count 3.077 t table with a value of 2.880 and a value of 0.003 0.05. (2) Taste has a significant effect, with the result of t count 5,678 t table with a value of 2,880 and a value of ,000 0,000 0.05. (3) Price also has a significant effect, with a negative t count result of 3.115 t table 2.880 and a value of 0.002 0.05. Packaging, taste and price have an effect simultaneously with the results of the f count 14.231 f table Significance value